Effect Of Monetary Policy Rates and Inflation on The Nigerian Exchange Group (NGX) - Adewale, Abass Adekunle (Kerbala International Journal of Management and Economics, 2025)
This study examines the impact of central bank monetary policy rates and inflation on stock market performance in Nigeria over the period 1990 to 2023. Using the All-Share Index (ASI) as a proxy for market performance, the study employs the Autoregressive Distributed Lag (ARDL) model to assess both short-run and long-run relationships among the variables. The Treasury Bill Rate (TBR) is utilized as a proxy for the central bank's policy rate, while a dummy variable is introduced to capture structural policy shifts from 2006 onwards. Findings reveal that both the monetary policy rate and inflation exert negative but statistically insignificant effects on stock market performance in the short and long run, suggesting limited direct influence of these macroeconomic tools on market behavior. In contrast, the exchange rate demonstrates a statistically significant and positive long-run effect on ASI, highlighting the potential influence of currency valuation on market outcomes. The results imply that Nigeria’s stock market may be more responsive to other structural or external factors than to conventional policy instruments. This study offers valuable insights for policymakers and investors, indicating the need for complementary reforms to enhance the efficacy of monetary policy in stimulating capital market growth.